Perception of Investors towards Dividends, Retained Earnings and Share Prices in Nepal - Awale , Ramita; Rwegasira, Kami S.P. (PYC Nepal Journal of Management, 2012)
This paper examines the attractiveness of dividends as opposed to retained earnings as well as the factors affecting market share price in Nepal. The primary data is used to meet the objectives of the study. The outcome of this paper suggests that the investors in Nepal prefer dividends to retained earnings because dividends portray information to shareholders that the company is doing better. The factor of earnings of the company is the most important factor that affects the share price in Nepal. On the other hand, the experience of managing director is the least important factor affecting share price which is in contrast to the other previous studies results.